Inelastic energy loss of Ar ions scattered Al2O3 surface under grazing incidence - Ashirov, A.S.; Qurbanov, M.K.; Tangribergenov, I.U.; Karimov, M.K.; Otabaeva, K.U. (Physics and Chemistry of Solid State, 2021)
In this paper presents the investigation of the surface Al2O3 by ion scattering spectroscopy. The trajectory of small angle scattered ions calculated by the method of binary collision approximation. It was found dependence of inelastic energy loss and trajectories of scattered ions. The value of inelastic energy loss scattered ions almost depend to the angle of incidence and the geometrical parameters of surface semichannels.